2000
DOI: 10.1590/s1415-47572000000200033
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating different proportions of exotic maize germplasm into two adapted populations

Abstract: Maize breeders frequently wish to use exotic germplasm in their breeding programs without losing specific characteristics of their adapted material. The objective of this study was to determine the optimal proportions of exotic germplasm to incorporate into adapted populations (F2 = 50% exotic, BC1 = 25% exotic, BC2 = 12.5% exotic and BC3 = 6.25% exotic) to form the initial foundation population and to determine the heterosis between adapted x exotics. We used six exotic populations of different origins and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Dudley (1982) suggested that backcrossing one or more times to the elite line was useful for selecting improved offspring. Santos et al (2000) conducted a systematic study and found that the best exotic proportions were 6.25 and 12.5%. Our results from this study are highly consistent with the conclusion of Santos et al (2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dudley (1982) suggested that backcrossing one or more times to the elite line was useful for selecting improved offspring. Santos et al (2000) conducted a systematic study and found that the best exotic proportions were 6.25 and 12.5%. Our results from this study are highly consistent with the conclusion of Santos et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al (2000) conducted a systematic study and found that the best exotic proportions were 6.25 and 12.5%. Our results from this study are highly consistent with the conclusion of Santos et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…It may be that pushing the yield of elite composites can be diffi cult through further composite formation via full crosses because the F 1 yields are often no higher than that of the elite parent and because the average parent yield is usually lower than the elite composite per se. However, dos Santos et al (2000) found that smaller proportions of exotic germplasm (12.5% vs. 50%) in a backcrossed population could signifi cantly increase the yield of elite composite populations (BR105, +15%; BR106, +4.4%) when the number of favorable alleles in the exotic populations was low. Apparently there are times when the careful addition of select alleles through backcrossing will make progress for yield of an elite composite as is often practiced with elite inbred lines used to form high yielding single cross hybrids (Troyer, 2000).…”
Section: Composite Populationsmentioning
confidence: 99%
“…), including exotics, may be a recommended strategy for the conditions of the vast array of environments like those occurring in Brazil. Exotic germplasm has largely contributed to increase the variability and the efficiency of breeding programs for the development of cultivars REGITANO NETO et al, 1997;SANTOS et al, 2000). The development of commercial hybrids initiated with local germplasm represented by old varieties such as Cateto and Dente Paulista.…”
Section: Introductionmentioning
confidence: 99%